OP0273 Does Spinal MRI Add Incremental Diagnostic Value to MRI of the Sacroiliac Joints Alone in Non-Radiographic Axial Spondyloarthritis?. (23rd January 2014) - Weber, U.; Zubler, V.; Zhao, Z.; Lambert, R. G.; Chan, S. M.; Pedersen, S. J.; Ostergaard, M.; Maksymowych, W. P.
Abstract : Background: The definition of a positive MRI as major criterion in the Assessment of SpondyloArthritis classification criteria for axial spondyloarthritis (SpA) is based on MRI of the sacroiliac joints (SIJ) alone. It is not known whether additional MRI of the spine may enhance diagnostic certainty over and above SIJ MRI alone. Objectives: To assess the incremental diagnostic value of spinal MRI evaluated both separately from and combined with SIJ MRI in non-radiographic SpA (nr-axSpA) compared to SIJ MRI alone. Methods: The study sample comprised 2 independent cohorts A/B of 130 consecutive patients with back pain ≤50 years newly referred to 2 university clinics, and 20 healthy controls (HC), in whom both SIJ and spinal MRI were available. Patients were classified according to clinical examination and pelvic radiography as having nr-axSpA (n=50), ankylosing spondylitis (AS; n=33), or mechanical back pain (MBP; n=47). SIJ and spinal MRI were assessed by 3 blinded readers according to standardized modules. Readers recorded presence/absence of SpA and their level of confidence in this conclusion by global evaluation of the MRI scans (T1SE and STIR sequences) on a 0-10 scale (0 = definitely not SpA; 10 = definite SpA). SIJ alone and spinal MRI alone were read independently 6 months apart, with another interval of 1-12 months to the combined assessment of both SIJ and spinal MRI. We analysed differences between SIJ alone versus spinal MRI alone, and SIJ alone versus combined read of SIJ and spinal MRI. This was done descriptively by the percentage (number) of subjects according to the mean of 3 readers for SIJ MRI and spinal MRI separately, and for combined MRI. Results: For cohorts A/B, 15.8%/28.0% of nr-axSpA patients considered having a negative SIJ MRI were re-classified as being positive for SpA by global evaluation of combined SIJ and spinal scans. However, 28.6%/11.1% of MBP controls and 18.3% of healthy volunteers, who showed a negative SIJ MRI, were falsely re-classified as having SpA by combined SIJ and spinal MRI. Low confidence (5-7) in a diagnosis of SpA by global evaluation of SIJ MRI increased to high confidence (8-10) by combined MRI in 3.5% and 8.6% of nr-axSpA patients in the 2 cohorts. Percentage of subjects (mean of 3 readers) Conclusions: Combined spinal and SIJ MRI added little incremental value compared to SIJ MRI alone for diagnosing nr-axSpA patients and enhancing confidence in this diagnosis. Disclosure of Interest: None Declared